2010
DOI: 10.1097/jcp.0b013e3181d41f41
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Benzodiazepine Use and Salivary Cortisol

Abstract: Despite the finding of slightly lower evening cortisol levels in daily and infrequent BZD users compared to nonusers, results indicate that long-term BZD use is not convincingly associated with HPA axis alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…Moreover, it is important to highlight that all patients were under benzodiazepines during this study and that half of them were already using them before the study. However, previous treatment with benzodiazepines did not predict CAR, corroborating some similar studies that did not observe changes in CAR induced by benzodiazepines (McIntyre et al, 1993;Manthey et al, 2010). Benzodiazepine modulation on the HPA axis is conflicting and dependent on the type of drug, dose, type of biological sample, and study design (Laakmann et al, 1984;Kalogeras et al, 1990;Pomara et al, 2005;Fries et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, it is important to highlight that all patients were under benzodiazepines during this study and that half of them were already using them before the study. However, previous treatment with benzodiazepines did not predict CAR, corroborating some similar studies that did not observe changes in CAR induced by benzodiazepines (McIntyre et al, 1993;Manthey et al, 2010). Benzodiazepine modulation on the HPA axis is conflicting and dependent on the type of drug, dose, type of biological sample, and study design (Laakmann et al, 1984;Kalogeras et al, 1990;Pomara et al, 2005;Fries et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…In our hands, we observed an ameliorating effect of imepitoin on cortisol levels in response to thunderstorm noises, but not for dexmedetomidine. Benzodiazepines were found to suppress cortisol levels ( Manthey et al, 2010 ), and thus these findings further support the benzodiazepine-like anxiolytic effect of imepitoin.…”
Section: Discussionmentioning
confidence: 55%
“…As BZDs have anxioliytic and sedating properties, it is expected that they influence the stress system. Also, most studies showed a decrease in cortisol levels, 39–43 some studies reported mixed results, 43–45 and these inconsistencies may be explained by differences in patient groups, dosages, and BZD used among studies. 43 Some studies yield a reduction of variations in noradrenaline (NA) metabolite levels (MHPG) ‘noradrenergic volatility’, 46 and in circulating and salivary cortisol levels using alprazolam in anxious patients 22 39 41 and in normal subjects, 47 or also an increase in levels of dehydroepiandrosterone (an anticortisol mediator).…”
Section: Introductionmentioning
confidence: 99%
“…Also, most studies showed a decrease in cortisol levels, 39–43 some studies reported mixed results, 43–45 and these inconsistencies may be explained by differences in patient groups, dosages, and BZD used among studies. 43 Some studies yield a reduction of variations in noradrenaline (NA) metabolite levels (MHPG) ‘noradrenergic volatility’, 46 and in circulating and salivary cortisol levels using alprazolam in anxious patients 22 39 41 and in normal subjects, 47 or also an increase in levels of dehydroepiandrosterone (an anticortisol mediator). 48 Nevertheless, many controversial findings were made depending on age and gender: younger anxious patients showed higher levels of salivary cortisol awakening response, 13 18 but other authors found high salivary cortisol levels associated with severity of late-life generalised anxiety disorders in older adults.…”
Section: Introductionmentioning
confidence: 99%